Information Literacy Learning Environment of Primary Schools in Iran: An Exploratory Study - Somayeh Akhshik; Mohammad Zerehsaz; Babak Dashti Garmi (International Journal of Information Science and Management, 2023)
This study aims to identify the characteristics of the information literacy learning environment (ILLE) for primary school students in Iran. This research was done by qualitative method and using content analysis. The statistical population was divided into two parts: 1) literature related to the INTE and 2) experts in the field of Information Literacy (IL). A researcher-made checklist was used to collect information in the first part, which was exploratory. The data collection tool from the second part of the community was the Delphi panel questionnaire, which was implemented in two stages. The results showed that ILLE has four dimensions for primary school students in Iran: educator, school library, classroom space, and educational resources. Considering these dimensions, categories, and sub-categories, it can be expected that a suitable environment will be provided for implementing IL programs in primary schools in Iran. Training administrators, curriculum developers, and information literacy educators can use this study's findings to improve ILLE to develop students with information literacy skills. This study is the first comprehensive study conducted in Iran that sought to identify the ILLE for primary school students. The findings are useful in providing a suitable environment for IL within schools in Iran and other countries.